Komunikasi Pembangunan dengan Aksentuasi Komunikasi Politik - B. Aly (Jurnal Komunikasi Pembangunan, 2010)
Communication development in globalization era is getting more and more important and significant since everyparty and the stakeholders have to work hand in hand in fair and honest way to achieve a better quality of socialorder. All parties and the stakeholders can optimize their part if they have intellectual vision, make good use of theinformation networking, and keep a good relation with everyone. Political communication approach demands thepolitical elite and the community leader to care and commit themselve to the betterment of the nation. The main pointis the communication development is airing at improving the life quality of everyone in every level of life.